Synthesis of Multivalent Carbohydrate‐Centered Glycoclusters as Nanomolar Ligands of the Bacterial Lectin LecA from Pseudomonas aeruginosa. Issue 28 (11th June 2013) - Gening, Marina L.; Titov, Denis V.; Cecioni, Samy; Audfray, Aymeric; Gerbst, Alexey G.; Tsvetkov, Yury E.; Krylov, Vadim B.; Imberty, Anne; Nifantiev, Nikolay E.; Vidal, Sébastien
Abstract: A family of fifteen glycoclusters based on a cyclic oligo‐(1→6)‐β‐D ‐glucosamine core has been designed as potential inhibitors of the bacterial lectin LecA with various valencies (from 2 to 4) and linkers. Evaluation of their binding properties towards LecA has been performed by a combination of hemagglutination inhibition assays (HIA), enzyme‐linked lectin assays (ELLA), and isothermal titration microcalorimetry (ITC). Divalent ligands displayed dissociation constants in the sub‐micromolar range and tetravalent ligands displayed low nanomolar affinities for this lectin. The influence of the linker could also be demonstrated; aromatic moieties are the best scaffolds for binding to the lectin. The affinities observed in vitro were then correlated with molecular models to rationalize the possible binding modes of these glycoclusters with the bacterial lectin. Abstract : Glycoclusters : Glycoclusters based on a cyclic oligo‐(1→6)‐β‐D ‐glucosamine core were synthesized as ligands of the bacterial lectin LecA (see figure). Divalent ligands displayed K d values in the sub‐micromolar range and tetravalent ligands displayed low nanomolar affinities. The introduction of an aromatic linker provided the best scaffold for binding to the lectin. The affinities observed could be correlated with molecular models.